A Quantitative Examination of Current Account Dynamics in Equilibrium Models of Barter Economies - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 1992)
This paper provides a numerical analysis of an intertemporal equilibrium model of a small open, barter economy that is subject to random shocks affecting endowments, the terms of trade, and the real interest rate. Equilibrium stochastic processes for macroeconomic aggregates are computed and their properties are compared with observed stylized facts. The model mimics the Harberger-Laursen-Metzler effect, but cannot account for a countercyclical trade balance, the variability of the real exchange rate, and the income elasticity of imports. The results also show that the correlation between the trade balance and the terms of trade, given incomplete insurance markets, is sensitive to changes in preference parameters and in the persistence of exogenous shocks.